2010
DOI: 10.1128/aem.00944-10
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk from the Use of Roof-Harvested Rainwater in Southeast Queensland, Australia, as Potable or Nonpotable Water, Determined Using Quantitative Microbial Risk Assessment

Abstract: A total of 214 rainwater samples from 82 tanks were collected in urban Southeast Queensland (SEQ) in Australia and analyzed for the presence and numbers of zoonotic bacterial and protozoal pathogens using binary PCR and quantitative PCR (qPCR). Quantitative microbial risk assessment (QMRA) analysis was used to quantify the risk of infection associated with the exposure to potential pathogens from roof-harvested rainwater used as potable or nonpotable water. Of the 214 samples tested, 10.7%, 9.8%, 5.6%, and 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 41 publications
(56 reference statements)
1
108
2
Order By: Relevance
“…20 Analyses of the containers have shown distributions of pathogenic microbes in rainwater collection systems, though the risk to human health is less than clear. 21,22 A systematic review found that, in a pooled analysis, rainwater was associated with a reduced risk of illness compared with unimproved sources. 23 Comparing distance measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…20 Analyses of the containers have shown distributions of pathogenic microbes in rainwater collection systems, though the risk to human health is less than clear. 21,22 A systematic review found that, in a pooled analysis, rainwater was associated with a reduced risk of illness compared with unimproved sources. 23 Comparing distance measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although an indicator should be correlated with the presence of pathogens and have a similar survival profile to the ones it detects, sometimes the FIB concentrations are not always correlated with the concentration of pathogens. Some studies have demonstrated a low or absent correlation with the presence of pathogenic forms, e.g., protozoan parasites and enteric viruses, virions, endospores, (oo)cysts (Wu et al 2011), and a variable degree of correlation with viral and zoonotic pathogens (Ahmed et al 2010). This issue is generally attributed to the widely differing physiology, phylogeny and ecology of FIB and pathogens.…”
Section: Limitations Of Fib-based Guidelinesmentioning
confidence: 99%
“…Unlike some fully off-grid configurations implemented elsewhere [3,4], system configurations in the UK are supplemented by mains water supplies for potable water applications such as drinking, bathing and dishwashing. Germany has seen strong uptake of RWH technologies as reported by Partzsch [5] with 80,000 installations per annum and a total industry value of 340 million Euros.…”
Section: Rainwater Harvesting At Uk Housesmentioning
confidence: 99%